Effects of gastric bypass on FoxO1 expression in the liver and pancreas of diabetic rats. (2nd January 2016) - Chen, Zhixiong; Meng, Changyuan; Liu, Jiyuan; Zhang, Jun; Kou, Yao; Zhang, Liuping; Wang, Zhihong
Abstract: Aim : To explore the mechanism by which gastric bypass surgery (GBS) ameliorates type 2 diabetes mellitus (T2DM) by investigating whether FoxO1 (a transcription factor that plays a crucial role in the regulation of glycolipid metabolism) expression is altered in the liver and pancreatic islet cells in a rat model of GBS-treated T2DM. Methods : Sprague-Dawley rats were randomly divided into four groups ( n  = 10 rats each): diabetic rats treated by GBS (DM + GBS), diabetic rats subjected to sham operation (DM + sham), normal control rats (control), and diabetic rats without surgery (DM). Fasting levels of blood glucose (BG), insulin, and glucagon-like peptide-1 (GLP-1) were measured in all groups before and 4, 8, 16, and 24 weeks after operation. Rats were killed 24 weeks after surgery. Liver and pancreas expressions of FoxO1 were investigated by immunohistochemistry and Western blotting analyses. Results : In the DM + GBS group, fasting BG before and 24 weeks after surgery decreased from 20.2 ± 2.1 to 7.7 ± 1.1 mmol/L, respectively; fasting insulin showed no change (2.9 ± 0.1 and 3.0 ± 0.1 mU/L, respectively); and fasting GLP-1 increased from 8.7 ± 0.9 to 23.5 ± 0.2 pmol/L, respectively. Fasting BG levels after surgery in the DM + GBS group were significantly lower than those in the DM + sham and DM groups. FoxO1 expression levels in the liver and pancreatic islets of the DM + GBS group were reduced compared to those in the DM + sham and DM groups. FoxO1 in the pancreatic β-cells was expressed mainly in the cytoplasm. Conclusions : Gastric bypass may improve type 2 diabetes mellitus by changing FoxO1 expression in the liver and pancreatic islet cells.